Implementation of Village Fund Direct Cash Assistance Program Policy in Sungai Kakap District Kubu Raya District - Yulius Yohanes; Nahot Tua Parlindungan Sihaloho (Yayasan Ilomata, 2023)
This research aims to describe the implementation of the Direct Cash Assistance program policy sourced from the Village Fund in 2022 in Sungai Kakap District, Kubu Raya Regency. This study used qualitative research methods. The research location was carried out in Sungai Kakap District, Kubu Raya Regency. From the results of the research carried out, it is known that the implementation of Village Direct Cash Assistance (BLT-DD) has a few obstacles from the Central Government in distributing aid funds to the Village Government, but this can be overcome by doubling the aid, namely funds that are delayed in the following month so that in the year In 2022, the community will receive aid funds amounting to IDR 900,000 after the distribution of aid funds has been delayed for 3 months.